PENDIDIKAN KARAKTER DALAM NOVEL HARIMAU-HARIMAU KARYA MOCHTAR LUBIS (KAJIAN HERMENEUTIKA) - Aida Azis, Sitti; Hasim (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
The purpose of this study was to assess the value of educational character, culture and nationality in the novel Harimau-harimau by Mochtar Lubis. The method used in this study was designed based on the principle of qualitative descriptive method that collecting, processing, reducing, analyzing, and presenting data in an objective context in literature. The data collection technique was document examined byreading Harimau-Harimau by Mochtar Lubis as a whole then making note, identifying data and classifying data based on research focus. The results of this study described that The character of educational religion included: an honest, caring neighbor, and friendly.